Pemanfaatan Media Papan Bergambar dalam Pembelajaran Bahasa Inggris pada Siswa Kelas II SDK Mbomba - Rosadalima Ule; Maryano Musaputra; Baltasar Putra Gado (Masyarakat Mandiri : Jurnal Pengabdian dan Pembangunan Lokal, 2025)
This Community Service (PKM) aims to increase the effectiveness of English language learning in second grade students of Mbomba Catholic Elementary School through the utilization of picture board media. The background of this activity is the low interest and participation of students in learning English due to the limitations of interesting learning media. The implementation method uses a participatory and educational approach that involves students actively in activities such as picture matching games, guessing pictures, storytelling, and singing. The results of the activity show that the use of picture boards is able to attract students' attention, increase engagement, and strengthen memory of English vocabulary. Despite the short implementation time, students still showed good understanding. Picture board media proved to be effective, simple, economical, and suitable to be implemented in schools with limited facilities. This activity illustrates that an attractive and interactive visual approach can be a solution in improving the quality of English language learning at the primary school level.